OBSERVATIONS ON THE BREEDING, LARVAL DEVELOPMENT AND TAXONOMIC STATUS OF MACROBRACHIUM EQUIDENS (DANA, 1852) - Pillai, N N (Indian Journal of Fisheries, 2011)
Macrobrachium equidens collected from Cochin Backwaters (Kerala) is represented by two forms, stripicdand non-strijjed. Separate studies canied out on the breeding and larval development of these two formsindicated that no intcr-brecding between them take place. Further the distinct colour pattern characteristicof these forms became discernible as the post-larvae grew to a size of 20-25 mm. The observationslend support for the consideration of these two forms as distinct spcdcs